Desarrollo de un plan de acción a corto, mediano y largo plazo para la incorporación de la cultura de administración de proyectos en la subgerencia general de operaciones del Banco Popular - Ramírez-Mora, Inés Priscilla (Instituto Tecnológico de Costa Rica, 2013)
The main objective of General Submanagement of Operations of Banco Popular is to guarantee in agreement with their areas that has in their supervision, the compliance of their objectives and goals according with the Corporate Strategic Plan which is related to their service areas. The present project has been aim to deliver an action plan in long, medium and short terms to develop and maintain a culture of project administration in the operations management. One way to define the project´s culture in an organization is through the application of maturity model, which is used to define levels of growth and development of the company in terms of its policies, practices, processes and procedures The application of maturity model, has been used to the analysis of results of the institutional methodology, which is an evaluation to determine the level of maturity and the sensitization of the project´s culture, which is based in Project Management Maturity Model (PMMM) by Harold Kerzner, addition to the application of other instruments that helped confirm the results attained. Once the analysis of the results it has done, it shows that exist an immaturity in the project management of the General Operations Management, which affect negatively in the performance of the projects and other activities that are developed at present.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2013.
Keywords: Planeamiento estratégico; Gestión de proyectos; Procedimientos; Organización; Desarrollo